2022
DOI: 10.1029/2021gl097548
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Prediction of Scattering Properties of Spheroidal Dust Particles With Machine Learning

Abstract: Dust aerosol has a widespread impact on air quality and visibility (Huang et al., 2008;Moulin et al., 1998) and modulates the Earth's radiation budget (Pachauri et al., 2014) via scattering and absorbing both shortwave and thermal infrared radiation (Xu et al., 2017), leading to large uncertainties in climate projection. The radiative forcing and spectral fingerprints of dust particles depend on their bulk optical properties, including the extinction coefficient, single-scattering albedo, and phase matrix. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…6 Recently, NNs have also been used for the calculation of the scattering properties of spheroidal aerosols with prospects for applications to cosmic dust studies. 14,15 However, despite the great potential of NNs, only a few studies have been reported about their use for the characterization of microplastics. 16−19 The widespread presence of plastic debris in terrestrial and aquatic environments has caused growing concern in the past decade and stimulated both political and scientific debate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 Recently, NNs have also been used for the calculation of the scattering properties of spheroidal aerosols with prospects for applications to cosmic dust studies. 14,15 However, despite the great potential of NNs, only a few studies have been reported about their use for the characterization of microplastics. 16−19 The widespread presence of plastic debris in terrestrial and aquatic environments has caused growing concern in the past decade and stimulated both political and scientific debate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The DNN method has emerged as a more viable solution, offering efficient computations and significantly smaller storage requirements for network parameters than the original database. For example, deep learning methods have already been applied to predict the single‐scattering properties and derivatives of dust aerosols (Chen et al., 2022; Yu et al., 2022). In the case of bare BC aggregates, a support vector machine method has been utilized for direct parameterization, establishing a relationship between optical properties and particle morphology (Luo, Zhang, Wang, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Scattering for a non-spherical particle of large size can be solved by approximate methods, such as the physical-geometric optics method (PGOM), that require fewer computational resources than rigorous methods [20]. The fundamental integral and differential single scattering properties required for radiative transfer computation can be generated using these algorithms or obtained using deep learning approaches [21,22]. Plenty of single scattering property databases for application in remote sensing and the simulation of radiative transfer have been developed to satisfy spectral and scale continuity, and they employ a variety of algorithms, such as those of the Lorenz-Mie theory [23][24][25][26], the discrete dipole approximation [26][27][28], the T-matrix methods [25,[28][29][30][31][32], the geometric optics method [33][34][35][36][37], the finite-difference time-domain method [35,38], etc.…”
Section: Introductionmentioning
confidence: 99%